Piriqueta pampeana, a new species of Turneraceae (Passifloraceae s.l.) from Rio Grande do Sul, Brazil - Cabreira, Thaíssa Nunes; Facco, Marlon Garlet; Miotto, Silvia Teresinha Sfoggia (Phytotaxa, 2015)
Piriqueta pampeana, a new species of Turneraceae, is described and illustrated here. The species occurs in the municipalities of Alegrete, Maçambará, Manoel Viana and São Francisco de Assis, in the western region of Rio Grande do Sul state, Brazil. It resembles Piriqueta suborbicularis and Piriqueta taubatensis, but can be distinguished by the presence of a pair of discoid basilaminar nectaries, a pair of petiolar nectaries and small nectaries distributed along the leaf margin, sepals with acute apex and a yellow spot at the base of the petals. Due to the intense environmental degradation of its habitat, and according to IUCN guidelines, we ranked the species as “Endangered” (EN).